2013
DOI: 10.4244/eijv9i7a133
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery bypass graft versus percutaneous coronary intervention with drug-eluting stent implantation for diabetic patients with unprotected left main coronary artery disease: the D-DELTA registry

Abstract: In diabetic patients with ULMCA disease with/without concomitant multivessel disease, PCI and CABG led to similar results in terms of death, MI and CVA. However, CABG was associated with less MACCE at long-term follow-up, primarily due to the higher repeat revascularisation rate with DES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Furthermore, a total of 6 observational studies, including 9360 patients with a mean weighted follow-up of 5.2 years were analyzed [24][25][26][27][28][29]. Of these total patients, 4237 patients (45.3%) were treated by DES-based PCI, and 3669 (39.2%) had DM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a total of 6 observational studies, including 9360 patients with a mean weighted follow-up of 5.2 years were analyzed [24][25][26][27][28][29]. Of these total patients, 4237 patients (45.3%) were treated by DES-based PCI, and 3669 (39.2%) had DM.…”
Section: Resultsmentioning
confidence: 99%
“…While much information is available regarding outcome definitions for RCTs, observational studies provided less detail and may have been a source of heterogeneity for outcomes other than all-cause mortality. Third, several observational studies had violations of the proportional hazards assumption as CABG may provide more significant benefit during longer follow-ups [24,25,27,29]. However, calculating the restricted mean survival time was not possible without the published adjusted survival curves or individual participant data [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous subgroup studies of individual randomized trials have attempted to address this issue, they have had limited power in isolation. [3][4][5] Moreover, registry-based studies have been constrained by a high risk of bias and confounding, [6][7][8][9] and no randomized controlled trials have specifically explored this key clinical question. Previous trials comparing PCI and CABG in patients with multivessel disease without left main involvement have suggested that diabetes might be a modulating factor for clinical outcomes, as evidenced by a lower 5-year mortality rate in patients with diabetes after CABG but similar 5-year mortality rate after PCI and CABG in patients without diabetes.…”
mentioning
confidence: 99%